A tool to visualize and analyze perfusion data: Development and application of the R package "CTP". (January 2018) - Lirette, Seth T.; Smith, Andrew D.; Aban, Inmaculada B.
Highlights: An open-source tool for creating perfusion maps is proposed. The tool is written and called completely within the R computing environment. Perfusion maps are validated through a digital phantom. The package is freely available on Github. Abstract: Background and objective: Computed tomography perfusion (CTP) is a widely used imaging modality especially in neuroimaging. Despite this, CTP is often prohibitive due to the dearth of free/open-source software. This could have wide-ranging implications for instruction and research. We have implemented an online-available CTP tool built and run completely within the R computing environment. Methods: Called from within R, the user can select one of four different methods to construct a cerebral blood flow (CBF) map: (1) max-slope (2) singular value decomposition (3) block circulant singular value decomposition or (4) oscillation minimization singular value decomposition. The four methods are compared against a digital CBF phantom. Results: All four methods generate a CBF map, with the oscillation minimization technique giving the most accurate map. Conclusions: We have constructed an easily accessible teaching and research tool to create a CBF map and made it freely available. We hope this tool will help facilitate understanding of the methods involved in constructing perfusion maps and be a valuable resource to future researchers.